2021
DOI: 10.1073/pnas.2014188118
|View full text |Cite
|
Sign up to set email alerts
|

TIA1 potentiates tau phase separation and promotes generation of toxic oligomeric tau

Abstract: Tau protein plays an important role in the biology of stress granules and in the stress response of neurons, but the nature of these biochemical interactions is not known. Here we show that the interaction of tau with RNA and the RNA binding protein TIA1 is sufficient to drive phase separation of tau at physiological concentrations, without the requirement for artificial crowding agents such as polyethylene glycol (PEG). We further show that phase separation of tau in the presence of RNA and TIA1 generates abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 71 publications
2
65
1
Order By: Relevance
“…Recent studies of other nuclear speckle resident proteins revealed that the nuclear speckle resident RNA nucleases parn-1 /PARN and parn-2 /TOE1 play distinct roles in tau toxicity [ 15 ]. Contemporaneous work from other laboratories has also implicated RNA-binding proteins in tauopathy, including Musashi (MSI) and T-cell intracellular antigen 1 (TIA1); while they have divergent RNA-binding functions, both TIA1 and MSI co-localize with tau-containing cytoplasmic lesions and modulate tau aggregation and concomitant tauopathy phenotypes in model systems [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of other nuclear speckle resident proteins revealed that the nuclear speckle resident RNA nucleases parn-1 /PARN and parn-2 /TOE1 play distinct roles in tau toxicity [ 15 ]. Contemporaneous work from other laboratories has also implicated RNA-binding proteins in tauopathy, including Musashi (MSI) and T-cell intracellular antigen 1 (TIA1); while they have divergent RNA-binding functions, both TIA1 and MSI co-localize with tau-containing cytoplasmic lesions and modulate tau aggregation and concomitant tauopathy phenotypes in model systems [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tau LLPS is regulated by intermolecular electrostatic interactions [ 12 ] and post-translational modifications, such as phosphorylation [ 7 , 13 ] and acetylation [ 14 ]. The RNA and RNA binding protein TIA1 can also interact with tau to drive tau LLPS [ 15 ]. The C -terminal microtubule-binding repeats of tau are the aggregation-prone region [ 16 ], which are believed to facilitate tau aggregation and play a crucial role in the formation of neurofibrillary tangles in Alzheimer’s disease (AD).…”
Section: Introductionmentioning
confidence: 99%
“…RBM45 acts as a component of the spliceosome, and its splicing process is regulated by miR-4454 in response to insulin signaling in a cell type-dependent manner, although such regulation has been reported only in the prostate glands so far [163]. The direct interaction of tau with TIA1 in the presence of RNA promotes the phase separation of tau and the formation of toxic oligomeric tau [164]. TIA1 plays an important role in the translational silencing of Methyl CpG-binding protein 2 (MECP2), which is important for normal brain development and physiology, in combination with Pummilio1, which recruits miR-200a and -302c, while HuC, instead of TIA1, predominates in neurons, resulting in a switch to translational enhancement [165].…”
Section: Alzheimer's Diseasementioning
confidence: 99%